Associations between gender norms and HIV self-efficacy among Latina immigrants in a farmworker community. Issue 1 (2nd January 2022) - Ravelo, Gira J.; Sanchez, Mariana; Cyrus, Elena; De La Rosa, Mario; Peragallo, Nilda; Rojas, Patria
ABSTRACT: Latina immigrant farmworkers are a vulnerable and understudied population that face a host of socio-cultural and structural barriers that place them at risk for HIV infection. Cultural factors, including traditional gender roles (egalitarian and marianismo) that frequently inhibit communication between partners and promote rigid roles, may particularly affect self-efficacy for HIV prevention among this population. Objective : This study examines the impact of women's gender norms on HIV knowledge and safe sex negotiation skills, along with the moderating influence of HIV self-efficacy among Latina immigrants in a farmworker community. Design : The current cross-sectional analysis study examines data from a sample ( N  = 157) of mostly undocumented Latina immigrant farmworkers in South Miami-Dade County, Florida. Analysis was performed on secondary data obtained from baseline collected on an intervention pilot study. Measures of traditional American (egalitarian) and Latina ( marianismo ) gender norms, HIV self-efficacy, and HIV knowledge, as well as key demographic variables were collected. Results : Findings revealed higher American (egalitarian) gender norms directly and indirectly predict higher HIV prevention factors. Additionally, HIV self-efficacy did not mediate effects of marianismo on HIV risk. Conclusion : Findings conclude that HIV prevention can be especially challenging due to socio-cultural and traditional gender norms faced by Latinas in farm working communities and that such norms should be taken into account when developing and adapting culturally appropriate interventions to reduce HIV related risk behaviors for Latinas residing in urban or farm working communities.